Peran Desain Kebijakan: Digitalisasi Penyiaran Televisi di Indonesia - Budi Agussetianingsih; Azhar Kasim (Kolaborasi : Jurnal Administrasi Publik, 2021)
The research was conducted with the aim of describing the policy of digitizing television broadcasts after the enactment of Law Number 11 of 2020 concerning Job Creation. The policy design tries to look at the design of the concept that was built and the practice to realize the broadcast digitization policy. The researcher uses an approach approach with the type of literature study research. Researchers conducted searches on various secondary data sources which were then processed to be described in the form of a literature study. The researcher conducted a data analysis based on the policy design theory by Birkland (2015) which discussed four elements of policy design, namely objectives, theories, instruments, and policy implementation processes. The results of the study indicate that the policy of digitizing television broadcasts should be stated holistically and its implementation involves the support of stakeholders. The policy design for television broadcast digitization has not yet been carried out with a comprehensive causal theory mapping so that the instruments and implementation processes are not yet ready to build the broadcast industry and the public to switch to digital television. To make this policy a success, this research can help the government to encourage digital technology for mapping important industrial strategies that are future-oriented and protect public needs, increase government incentive support, as well as inclusive involvement from institutions both central and local, as well as local non-government institutions in the transition process. Keywords: policy design, broadcast digitization, television. Penelitian dilakukan dengan tujuan untuk menggambarkan kebijakan digitalisasi penyiaran televisi setelah ditetapkannya Undang-Undang Nomor 11 Tahun 2020 Tentang Ciptakerja. Desain kebijakan mencoba untuk melihat perancangan konsep kebijakan yang dibangun serta praktik untuk mewujudkan tujuan kebijakan digitalisasi penyiaran. Peneliti menggunakan pendekatan kualitatif dengan jenis penelitian studi literatur. Peneliti melakukan penelusuran terhadap berbagai sumber data sekunder yang kemudian diolah untuk di deskripsikan kedalam bentuk studi literatur. Peneliti melakukan analisis data yang didasarkan pada teori desain kebijakan oleh Birkland (2015) yang difokuskan pada empat eleman desain kebijakan, yaitu tujuan, teori kausal, instrumen, dan proses implementasi kebijakan. Hasil penelitian menunjukkan bahwa kebijakan digitalisasi penyiaran televisi seharusnya dirumuskan secara holistik dan implementasinya melibatkan dukungan dari para pemangku kepentingan. Desain kebijakan digitalisasi penyiaran televisi belum diimbangi dengan pemetaan teori kausal yang komprehensif sehingga instrumen dan proses implementasi kebijakan belum sepenuhnya dipersiapkan untuk membangun industri penyiaran dan masyarakat untuk beralih ke televisi digital. Untuk mensukseskan peralihan teknologi digital diperlukan pemetaan strategi industri yang berorientasi masa depan dan melindungi kebutuhan publik, peningkatan dukungan insentif pemerintah, serta keterlibatan secara inklusif dari institusi pemerintah baik pusat dan daerah, serta institusi non-pemerintah daerah dalam proses transisi.